THE INFLUENCE OF SELF-EFFICACY, ENTREPRENEURIAL KNOWLEDGE, PARENTAL INCOME MODERATED BY PARENTAL OCCUPATION ON ENTREPRENEURIAL INTENTION AMONG STUDENTS OF STATE VOCATIONAL HIGH SCHOOLS IN CENTRAL BANGKA - Sartika Siahaan; Maimun Sholeh (International Journal of Teaching and Learning, 2025)
This study aims to determine (1) the effect of self-efficacy on students' entrepreneurial intentions, (2) the effect of entrepreneurial knowledge on students' entrepreneurial intentions (3) the effect of parental income on students' entrepreneurial intentions. (4) the influence of parents' work on students' entrepreneurial intentions (5) self-efficacy, entrepreneurial knowledge, and parental income moderated by parental work on entrepreneurial intentions. This research is an expost facto research with a quantitative approach. The study was conducted 296 student as respondents of XII SMK with 14 concentration major using the proportional area random sampling technique. The validation technique was observed using Confirmatory Factor Analysiss (CFA), the reliability test used Cronbach's alpha and the feasibility of the questions with Anbuso 6.1. The data was analysed using multiple linear regression techniques and Moderated Regression Analysis (MRA). The results of the study showed that self-efficacy was partially influential significantly and positive on students' entrepreneurial intentions of 26,6%. The entrepreneurial knowledge partially has significantly and positive effect on students' entrepreneurial intentions of 30,9%. The parental income partially has a significant and positive effect on students' entrepreneurial intentions of 1,380, (4) the work of entrepreneurial parents partially has significantly and positive effect on student entrepreneurial intentions of 4,669. (5) self-efficacy, entrepreneurial knowledge, and parental income could not be moderated by parental work on entrepreneurial intentions with a significance result of 0.016 and t count <t table namely 1,877<1,960. The multiple linear regression analysis showed the coefficient of determination (R square) was 0.395. Furthermore, the independent variables was consisting of self-efficacy, entrepreneurial knowledge, parental income, and parental work are 39.5% and the remaining 61.5% are influenced by another variable.